The Origination of Football and its Perspectives - Umurboevich , Rakhmatov Ulmas (Researchparks Publishing, 2023)
By the 19th century, especially by the middle of this century, a new stage in the history of football began after the sports method was recognized as the most appropriate method of physical education, and sports games became an effective means of physical development. The article highlights the history of the emergence and development of football, as well as the issues of popularization and uniqueness of football games. Also It can be assumed that in the times of Western Europe, such games were developed both independently and by learning some elements from each other in the middle of this century.